New sponge records (Porifera) from King George Island, Antarctica, including the description of Phorbas sp. nov. - Arteaga, Alvaro (2022)
Sponges are an important and abundant component of Antarctic marine ecosystems. They harbour a great diversity of species and play a key role in these fragile benthic communities. The aim of this study was to identify the sponges collected during the Peruvian scientific campaigns to Antarctica carried out in the austral summer of 2018 and 2019 (ANTAR XXV and ANTAR XXVI). Specimens were collected by van Veen grabbers and small dredges down to 215 m depth at Admiralty Bay, Maxwell Bay and the proximities of Bransfield Strait, along King George Island. Photographs and field notes were taken. After collection, the macroscopical features (colour, shape, surface characteristics and consistency) and the internal anatomy were assessed. Dissociated spicules and skeleton slides were prepared to characterise the shape and size of the spicules, and the type of skeleton organisation. Seven species, including four Demospongiae and three Hexactinellida, were identified. Mycale (Oxymycale) acerata Kirkpatrick, 1907 and Phorbas glaberrimus (Topsent, 1917) are new records for Mackellar Inlet (Admiralty Bay); Haliclona (Reniera) aff. altera (Topsent, 1901), Rossella antarctica Carter, 1872 and Rossella fibulata Schulze & Kirkpatrick, 1910 are firstly reported for Maxwell Bay; Rossella podagrosa Kirkpatrick, 1907 constitutes a new record for Maxwell Bay and Bransfield Strait; and Phorbas sp. nov. is new to science. Among the Antarctic species, Phorbas sp. nov. mostly resembles P. glaberrimus (Topsent, 1917) in spicule sizes (oxeas, acanthostyles and isochelae), but its morphology and skeleton organisation are different. Phorbas glaberrimus presents a massive shape and a choanosomal skeleton composed of multispicular fibres that end in a palisade at the ectosome; while, Phorbas sp. nov. has a ramose habit and a plumose choanosomal skeleton composed by spicules running towards a paratangential ectosomal skeleton. With this study, the number of sponge species recorded from King George Island raises to 36.